IL-1R8 silencing improves the anti-tumor function of freshly isolated human NK cells. Issue 3 (15th March 2022) - Landolina, Nadine; Mariotti, Francesca Romana; Ingegnere, Tiziano; Alicata, Claudia; Ricci, Biancamaria; Pelosi, Andrea; Veneziani, Irene; Azzarone, Bruno Giuseppe; Garlanda, Cecilia; Mantovani, Alberto; Moretta, Lorenzo; Maggi, Enrico
Abstract : The inhibitory receptor interleukin-1 receptor 8 (IL-1R8) has been recently recognized to be expressed also by human natural killer (NK) cells. This study was aimed to design and optimize IL-1R8 silencing conditions in human NK cells to precisely establish the activity of such receptor in these cells. Electroporation of freshly isolated or IL-2-cultured NK cells with small interfering RNA (siRNA), resulted in a marked, even though variable, IL-1R8-silencing. Although the expression profile revealed downregulation of most genes involved in several intracellular pathways, some genes related to proliferation, expression of some chemokine receptors, antibody-dependent cell cytotoxicity and cytotoxic activity were upregulated in IL-1R8-silenced NK cells. Furthermore, upon IL-15 activation, the majority of genes involved in NK cell function were upregulated in IL-1R8-siRNA—compared with control—siRNA-transfected NK cells. More importantly, in agreement with these findings, the reduction of IL-1R8 gene expression levels resulted in enhanced expression of NK cell activation markers, production of cytokines and chemokines, and cytotoxic activity against several NK cell targets with different susceptibility to NK-mediated lysis. Similar results were obtained following stimulation with IL-18. All together these data, deeply impacting on the main effector functions of human NK cells, can lead to a better understanding of IL-1R8-mediated regulation on these cells and to the design of new strategies for improving NK cell-mediated anti-tumor responses.